Social Map Of The Language: Neurolinguistics And Optimization Of Speech - Raufovna, Sayfullaeva Rano; Radjabovich, Bobokalonov Ramazon; Ikromovna, Hayitova Nigina (International Journal of Psychosocial Rehabilitation, 2020)
: This article present analyses for a role of the modern neurolinguistics for the linguistics and methodic of teaching to French language consist of forming communicative skills, which plays a huge part at studying process. There are main directions of the neurolinguistic researches; their importance to the linguistics is reflected. The following article deals with the problems of making up sentences in semantic- functional canonic models. In addition, one of the problems of Uzbek and French languages syntaxes speech differentiation in comparison aspect from the spiritual education.